Plug-and-play QKD architecture with a self-optical pulse train generator - Woo, Min Ki; Park, Chang Hoon; Park, Byung Kwon; Jung, Hojoong; Kang, Dongyeon; Jeon, Seung-Woo; Kim, Sangin; Han, Sang-Wook (Optical Society of America, 2022)
The commercialization of quantum key distribution (QKD), which enables secure communication even in the era of quantum computers, has acquired significant interest. In particular, plug-and-play (PnP) QKD has garnered considerable attention owing to its advantage in system stabilization. However, a PnP QKD system has limitations on miniaturization owing to a bulky storage line (SL) of tens of kilometers. And, the secure key rate is relatively low because Bob transmits the signal pulses only at the dedicated time slots to circumvent backscattering noise. This study proposes a new method that can eliminate the SL by realizing an optical pulse train generator based on an optical cavity structure. Our method allows Alice to generate optical pulse trains herself by duplicating Bob's seed pulse and excludes the need for Bob's strong signal pulses that trigger backscattering noise as much as the conventional PnP QKD. Accordingly, our method can naturally overcome the miniaturization limitation and the slow secure key rate, as the storage line is no longer necessary. We conducted a proof-of-concept experiment using our method and achieved a key generation rate of 1.6x10(-3) count/pulse and quantum bit error rate <= 5%. (C) 2022 Optica Publishing Group under the terms of the Optica Open Access Publishing Agreement